The Peningkatan Kualitas Layanan Pada Apotek Menggunakan Metode Servqual dan Service Blueprint - Alfandy Alif Utama; Elly Wuryaningtyas Yunitasari; Kusmendar Kusmendar (Program Studi Teknik Industri Universitas Setia Budi, 2025)
Depok Sleman Pharmacy, which has been established since early 2000, is now facing stiff competition from many new competitors, especially franchises with modern and complete services, where service quality is a crucial competitive aspect that has a direct impact on customer satisfaction. Therefore, this study aims to convey the level of customer satisfaction at this pharmacy and formulate service improvement proposals to remain competitive and not appear to be left behind in service facilities. In achieving this goal, the study uses two main methods: the first method is Servqual, which is used to analyze customer satisfaction by measuring the gap between customer expectations and perceptions of five service dimensions, and because the measurement results indicate a negative gap (performance below expectations), it is continued with the stage of formulating improvement proposals using the second method, namely service blueprint, which functions to visualize the entire service flow, including customer interactions (frontstage) and support processes (backstage), in order to address the identified gap points. Data were collected through a physical questionnaire distributed to 100 Depok Pharmacy customers who made in-person transactions on-site between December 2024 and January 2025. The results showed that 19 of the 22 service attributes had a negative gap value, and the overall service quality calculation resulted in a score of 0.964, indicating that most services did not meet customer expectations. Based on these findings, a service blueprint was designed as a proposal for comprehensive improvements to the service flow, in order to improve service quality and strengthen the pharmacy's presence amidst increasingly fierce competition.